Bacterial cellulose nanocrystals produced under different hydrolysis conditions: properties and morphological features - Vasconcelos, Niédja Fittipaldi (2017)
Bacterial cellulose (BC) is a polymer with interesting physical properties owing to the regular and uniform structure of its nanofibers, which are formed by amorphous (disordered) and crystalline (ordered) regions. Through hydrolysis with strong acids, it is possible to transform BC into a stable suspension of cellulose nanocrystals, adding new functionality to the material. The aim of this work was to evaluate the effects of inorganic acids on the production of BC nanocrystals (BCNCs). Acid hydrolysis was performed using different H2SO4 concentrations and reaction times, and combined hydrolysis with H2SO4 and HCl was also investigated. The obtained cellulose nanostructures were needle-like with lengths ranging between 622 and 1322 nm, and diameters ranging between 33.7 and 44.3 nm. The nanocrystals had a crystallinity index higher than native BC, and all BCNC suspensions exhibited zeta potential moduli greater than 30 mV, indicating good colloidal stability. The mixture of acids resulted in improved thermal stability without decreased crystallinity.